Assessing student performance in Digital Signal Processing (DSP) subjects: a comparative study of traditional and online learning environments / Mohd Rizman Sultan Mohd, Juliana Johari and Fazlina Ahmat Ruslan - Sultan Mohd, Mohd Rizman; Johari, Juliana; Ahmat Ruslan, Fazlina (UiTM Press, 2024)
This study compares traditional and online learning environments to evaluate students’ performance in Digital Signal Processing (DSP). Online learning had become an option for the delivery of the subject since the COVID-19 pandemic. As one of the core subjects in the Electrical Engineering course, there is a need to investigate the impact of the traditional and online learning environment methods on student performance for the DSP. There is a total of 100 participants in the assessment involving undergraduates from Electrical Engineering who completed the subject. Based on the results, 70% of the students choose to take the subject using traditional methods compared with the online learning environment. This study suggests that the student prefer to take DSP subjects in traditional classroom learning compared to the online learning environment.